2006
DOI: 10.1007/s11270-005-9032-7
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of the Phosphorus Retention Capacity of Wetlands in the Painter Creek Watershed, Minnesota, USA

Abstract: Lake Minnetonka, located in southeastern Minnesota, U.S.A., is currently experiencing increased eutrophication due to excessive phosphorus (P) loading in runoff from agriculture and urban areas. This phenomenon has been exacerbated by the isolation of wetlands in the surrounding watershed from the surface water drainage network. In order to determine if rerouting surface water through these wetlands would be a feasible method for reducing P inputs, we assessed the P retention capacity of wetlands in a subwater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 25 publications
1
35
1
Order By: Relevance
“…Richardson & Qian (1999) suggested that the P concentration in the outflow increases exponentially after a P loading threshold (1 g/m 2 /yr) has been exceeded, though wetlands may serve the function of reducing P transport to downstream water bodies even at higher loads than this. To be able to manage such wetlands for a sustained P retention, it is important to identify the dominant retention processes, whether it is sediment sorption of dissolved P (Bruland & Richardson, 2006), sedimentation of particulate P (Braskerud, 2002;Coveney et al, 2002;Koskiaho et al 2003) or biological P uptake, or a combination of all.…”
Section: Introductionmentioning
confidence: 99%
“…Richardson & Qian (1999) suggested that the P concentration in the outflow increases exponentially after a P loading threshold (1 g/m 2 /yr) has been exceeded, though wetlands may serve the function of reducing P transport to downstream water bodies even at higher loads than this. To be able to manage such wetlands for a sustained P retention, it is important to identify the dominant retention processes, whether it is sediment sorption of dissolved P (Bruland & Richardson, 2006), sedimentation of particulate P (Braskerud, 2002;Coveney et al, 2002;Koskiaho et al 2003) or biological P uptake, or a combination of all.…”
Section: Introductionmentioning
confidence: 99%
“…Qual. 35:1975-1982(2006 Reproduced from Journal of Environmental Quality. Published by ASA, CSSA, and SSSA.…”
mentioning
confidence: 99%
“…Phosphorus retention can decrease under reducing conditions in wetland soils with the release of P from Fe complexes following reduction of Fe from Fe +3 to Fe +2 (Patrick et al 1973), and under sufficiently reducing conditions, the binding of Fe by sulfides can further enhance P release (Brigham et al 2001;Caraco et al 1989). Under the anaerobic conditions needed for effective removal of NO 3 through denitrification, wetlands with high levels of calcite and exchangeable Ca are more likely to retain P due to insoluble, Ca-bound P (Bruland and Richardson 2006;Richardson 1999). However, wetlands can become P sources if sediments are remobilized (Mitsch et al 2005b), and additional research is needed to document the longterm effectiveness of wetlands as P sinks and to understand conditions under which stored P might be released.…”
Section: Figurementioning
confidence: 99%